Aprendizagem enriquecida por tecnologias no ensino de línguas: uma revisão do escopo na literatura internacional recente - (:unkn) unknown (Universidade Federal do Pampa, 2023)
It is a study that presents the review of works on language learning enriched by technologies, as digital resources are becoming present in language classes, even more so after the pandemic, which led to social distancing. This research work aims to report based on a scoping review, the contributions and challenges of Technology Enhanced Learning (TEL) for language teaching presented in recent international research, from 2020 to 2022, using the Web of Science database. From the 114 included articles, data analysis was conducted leading to the following results: social networks are the most used digital resources for language teaching. In addition, the researched articles emphasize the student, integrated skills are predominant in relation to other aspects of language development, the most prominent positive aspect was the improvement in linguistic skills through technologies, and insecurity or difficulty in using digital platforms was identified as a negative aspect. Finally, the importance of conducting research focused on the pedagogical practice of language teachers who adopt teaching methods through technologies is emphasized.
Keywords: TEL; Desenvolvimento linguístico; Revisão de Escopo; Technology Enhanced Learning; Linguistic development; Scoping review; LINGUISTICA, LETRAS E ARTES